UPAYA PEMENUHAN STANDAR NASIONAL PENDIDIKAN PROGRAM PENDIDIKAN KESETARAAN DI SATUAN PENDIDIKAN NONFORMAL SANGGAR KEGIATAN BELAJAR KUBU RAYA - Rita Rita; Syukri Syukri; Wahyudi Wahyudi (Universitas Tanjungpura, 2021)
AbstractThis study aims to describe the efforts to comply with content standards, process standards, and standards for educators and education personnel in the equivalency education program at SPNF SKB Kubu Raya Regency.This methods research uses a qualitative approach with a type of case study. The subjects of this study were the head of SPNF SKB Kubu Raya Regency, deputy head of learning affairs, deputy head of curriculum affairs, deputy head of community service, administration, and tutelary affairs. Data collection methods by interview, observation, and document study. Data analysis used interactive data analysis, namely data reduction, data display and verification. Checking the validity of the data using credibility, transferability, dependability, and confirmability tests. Conclusion of research results showed the following: (1) program planning begins with identifying the learning needs, (2) steps to fulfill SNP, (3) curriculum evaluation is carried out and according to the national curriculum structure, (4) supporting factors and inhibiting factors. There needs to be a commitment from the local government to allocate operational budgets for SPNF, improve facilities and infrastructure, and follow up on the evaluation of the development of the equality program at SPNF SKB Kubu Raya Regency.Keywords: Equality Education, Nonformal Educatio, SNP